Adoption or placement in foster care and catch-up in linear growth and development: A meta-analysis of individual participant data - Leroy, Jef L.; Angel, Moira Donahue; Frongillo, Edward A. (Elsevier, 2025)
Background The ability of children to recover from linear growth retardation, often referred to as catch-up growth, has intrigued researchers for many decades. Whether adoption from a low-to a high-income setting, which provides a comprehensive improvement in the conditions that cause children to not grow well, leads to catch-up growth is unknown.